Psychological Well-Being of Caregivers of Parents with Mental Illness: An Exploratory Study - Talib, Ansa; Ijaz, Adan (Applied Psychology Review, 2024)
The current study was conducted to explore the psychological well-being of caregivers having a parent with mental illness. The purposive sampling technique was used to conduct the study. A sample of 12 (8 women and 4 men) adults aged 18-40 years having parents with mental illness, such as schizophrenia, depression, and compulsive disorders were selected from the psychiatry ward of one of the government hospitals in Faisalabad, Pakistan. A focus group discussion was conducted through the trained facilitator. Thematic analysis was used to examine the data. Five major themes, namely significant impact on life, responsibilities, societal pressure, attention towards religion, personal, social and family dynamics, and nine sub themes, namely psychological impact, overall health affected, influence on academic performance, balancing caregiving and personal roles, social integration, religious strength, social life circumstances, family situation, emotions and feelings were extracted. The findings highlight the impact of parents’ mental illness on the well-being of adult caregivers in Pakistani context. Furthermore, findings may also help clinicians in tailoring the interventions accordingly to the context of the current study in order to enhance and improve caregivers’ well-being.